ANALYSIS OF THE EFFECT OF QUALITY COMPONENTS OF WEB 2.0 ENABLED E-COMMERCE WEBSITES ON ELECTRONIC WORD-OF-MOUTH MARKETING (EWOM) AND ON CUSTOMER LOYALTY - HARUN GUMUS; VEDAT BAL (Annals of the University of Oradea: Economic Science, 2016)
Electronic Word-of-Mouth Marketing (eWOM) has begun to play a more important role in customers’ purchasing decisions (Cheung and Thadani, 2012, Jones and Taylor, 2007). Previous studies reveal that eWOM increases the purchasing behavior of customers (Chevalier and Mayzlin, 2006). Nevertheless, despite its increasing importance, having limited literature on eWOM makes this subject attractive. Businesses want to bring customer behaviors under control by trying to give the meaning of eWOM messages. In this regard, businesses should observe the eWOM relationship by developing factors such as; aesthetics, content, orientability, system quality, information and content quality and service quality of websites. The aim of this study is to offer a model analyzing the relationship among the quality aspects of website, website loyalty and electronic word-of-mouth communication (eWOM) and to test this model